PENGARUH SISTEM PENGENDALIAN INTERNAL, PERILAKU TIDAK ETIS DAN BUDAYA ORGANISASI TERHADAP KECENDRUNGAN KECURANGAN (FRAUD) PADA LEMBAGA PEKREDITAN DESA (LPD) SE-KECAMATAN SUSUT - Ni Wayan Erika; Sang Ayu Putu Arie Indraswarawati (UNHI Press, 2022)
Fraud is a deliberate fraud that causes losses to other parties and provides benefits to the perpetrator of the fraud and / or his group. This study aims to determine the effect of internal control systems, unethical behavior, and organizational culture on the (fraud) tendency to cheat. This research was conducted at the Village Credit Institution (LPD) in Susut District. The sample in this study were 167 LPD employees. The sampling method used is proposive sampling. The data analysis technique used in this research is descriptive statistics, validity test, reliability test, classical assumption test, multiple linear regression, coefficient of determination, F test, and t test. From the results of this study that the internal control system variable has no effect on the tendency of fraud. The variable of unethical behavior has a positive and significant effect on the (fraud) tendency to cheat. Organizational culture variables have a negative and significant effect on the (fraud) tendency to cheat.